TECHNOLOGY OF CONSTRUCTION OF PATHS AND PLAYGROUNDS IN PARKS (American Journal of Interdisciplinary Research and Development, 2025)
This work discusses modern technologies and methods for the construction of paths and playgrounds in parks. The article covers the main stages of the construction process, such as marking the paths and playgrounds, preparing the base, selecting materials, establishing the profile, and working with high-quality concrete or paving tiles. Additionally, the factors that should be considered when constructing paths under different soil conditions and the careful selection of materials are discussed. The construction technologies used for paths and playgrounds in parks help create a stable and aesthetically pleasing environment for people.